Evolutionary history of mitogen-activated protein kinase (MAPK) genes in Lotus, Medicago, and Phaseolus - Neupane, Achal (Landes Bioscience, 2013)
Mitogen-Activated Protein Kinase (MAPK) genes encode proteins that mediate various signaling pathways associated with biotic and abiotic stress responses in eukaryotes. The MAPK genes form a 3-tier signal transduction cascade between cellular stimuli and physiological responses. Recent identification of soybean MAPKs and availability of genome sequences from other legume species allowed us to identify their MAPK genes. The main objectives of this study were to identify MAPKs in 3 legume species, Lotus japonicus, Medicago truncatula, and Phaseolus vulgaris, and to assess their phylogenetic relationships. We used approaches in comparative genomics for MAPK gene identification and named the newly identified genes following Arabidopsis MAPK nomenclature model. We identified 19, 18, and 15 MAPKs and 7, 4, and 9 MAPKKs in the genome of Lotus japonicus, Medicago truncatula, and Phaseolus vulgaris, respectively. Within clade placement of MAPKs and MAPKKs in the 3 legume species were consistent with those in soybean and Arabidopsis. Among 5 clades of MAPKs, 4 founder clades were consistent to MAPKs of other plant species and orthologs of MAPK genes in the fifth clade-"Clade E" were consistent with those in soybean. Our results also indicated that some gene duplication events might have occurred prior to eudicot-monocot divergence. Highly diversified MAPKs in soybean relative to those in 3 other legume species are attributable to the polyploidization events in soybean. The identification of the MAPK genes in the legume species is important for the legume crop improvement; and evolutionary relationships and functional divergence of these gene members provide insights into plant genome evolution.